Industrial Training Report: Program Pendidikan Khas Integrasi Kolej Tingkatan 6 Tunku Abdul Rahman Putra / Irwanni Mohamed Noh - Mohamed Noh, Irwanni (Faculty of Information Management, 2017)
During the making industrial training, PPKI department has asked to make a corporate video about the Special Education Integration Programe . Although the Special Education Program has existed in some specific schools, but there are still some who are less sensitive to the importance of sending their children to school. During my observation, there are some procedures that must be followed before a student is said to be worthy to enter the PPKI. Among them is the admission process requires a certificate from a qualified medical personnel using the special form provided. In addition, each student is eligible for special education receive a monthly allowance of RMI 50 and spending money is also under the control of teachers. These students are also divided into several categories of problems such as learning disabilities, mental retardation, autism, dyslexia and others. They also learn the same curriculum as students in the mainstream, but they also learned Modular Skills Certificate (SKM), bread-making and creative sewing. Students who have graduated, will be offered to further their studies in private colleges selected. For special project, the PPKI had no previous corporate video is used to introduce PKI to the guests. With corporate earnings this video, an introduction to PPKI can be made with simple, attractive and save time. Video applications used Scribe Video and Real Movie Maker. The use of two software is simple and attractive and clear to be understood by the people.